'Hard-Boiled' Detectives in Spain and Mexico: The Ethical Reorientation of a Genre. (September 2021) - Cafiero, Deborah
Abstract : Hard-boiled' fiction arose in the early decades of the twentieth century, uncovering connections among crime, wealth and power, and exposing moral fissures within U.S. capitalism. After French publisher Gallimard marketed translations of American crime fiction as noir, international writers started adjusting the ethical framework of the original authors as part of their 'glocal' adaptation of a global genre to local circumstances. The present article pushes past 'glocal' analysis of noir to propose a 'transnational' relationship, adapting Paul Giles' definition of 'transnational' practice in which international authors reflect the genre back upon its American roots in order to illuminate the 'silences, absences and blindspots' in the original ethical stance. The 'misreading' of noir also permits a 'misrecognition' of local circumstances, exposing moral fissures throughout different societies. This article shows how series by Manuel Vázquez Montalbán and Paco Ignacio Taibo II reveal ethical blindspots in American models by situating the detective within an emotional history of place (Barcelona for Vázquez Montalbán, Mexico City for Taibo II). Although these detectives ultimately cannot determine or perform the role of ethical citizen, their emotional-geographical bonds open up a critique of American ideals and pave the way for a reimagining of the ethical in the twenty-first century.